Yin yoga and mindfulness: a five week randomized controlled study evaluating the effects of the YOMI program on stress and worry. Issue 4 (4th July 2017) - Hylander, Frida; Johansson, Maria; Daukantaitė, Daiva; Ruggeri, Kai
ABSTRACT: Background and objectives: The YOMI program is a psychoeducational training and physical practice-based program that bridges knowledge from evidence-based psychotherapy with the practice of mindfulness and yin yoga. It consists of 10 content-specific sessions and does not include home assignments. The primary purpose of this randomized controlled trial is to evaluate the effects of the five-week YOMI program on perceived stress, worry and mindfulness in a non-clinical sample. Design and method: In this randomized controlled trial participants were assigned to two groups. Group 1 participated in the five-week intervention twice a week while Group 2 was assigned to a waiting-list condition and participated in the intervention after Group 1. All measures were administered through self-report questionnaires, conducted via a web-based program. Results and conclusions: The results of the study indicated significant effects of the YOMI program on decreasing stress and worry, and increasing mindfulness. Notably these changes were still present at five-week follow up. Consistent with the hypotheses, results suggested that the YOMI program established a group setting where individuals learned to use tools and methods to facilitate better self-directed practice. The study shows moderate to large effect sizes.